Pola Pendidikan Bangsa Israel sebagai Model dalam Penanaman Iman kepada Generasi Baru - Darmanto D (Sekolah Tinggi Theologia Nazarene Indonesia, 2017)
Education occupies an important position in the sustainability of a nation, so keep awake and not lose generation,(lose generation = a generation that does not believe in God). Israelites or Jews have a Pattern of education inherited from generation to generation to maintain the purity of their faith.Religion and dailly activities are not separated, Jews are believers and believe in one God; To keep it's parents teaching their childrens at home and in the community education by Jewish teachers (rabbi) in the synagogue.God instructs parents to teach their childrens and grandchildrens of the God in any time, any where; To keep the purity of a generation who fear God.